Crystal structure of (Z)-N-(17-(1-(dimethylamino)ethyl)-10,13-dimethyl-4-oxo-4,5,6,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-1H-cyclopenta-[a]phenanthren-3-yl)-3-methylbut-2-enimidic acid dichloromethane monosolvate, C29H45Cl2N2O2 - He Kang (Zeitschrift für Kristallographie - New Crystal Structures, 2013)
C29H45Cl2N2O2, monoclinic, P21 (no. 4), a = 8.4429(4) Å, b = 19.6901(9) Å, c = 9.0259(4) Å, β = 100.700(2)°, V = 1474.4 Å3, Z = 2, Rgt(F) = 0.0492, wRref(F2) = 0.1437, T = 293 K.